Improving Student Learning Outcomes in Islamic Education Learning through the Picture and Picture Learning Model at SD 13 Negeri Meulaboh - Fitri, Sah; Samsimar (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) through the application of the Picture and Picture model with the material of the exemplary story of the Prophet Ayyub (AS) and the Prophet Zulkifli (AS) in grade IV of SDN 13 Meulaboh. This study is a Classroom Action Research (CAR) conducted in two cycles with the stages of planning, action, observation, and reflection. The subjects of the study were 24 students who were selected because of the still low learning outcomes on the material studied. Data were collected through observation, tests, and documentation, then analyzed qualitatively and quantitatively. The results of the study showed a significant increase in student learning outcomes. In the pre-cycle, the learning completion rate only reached 54%, increased to 71% in cycle I, and finally reached 96% in cycle II. This increase was also supported by the increasing activeness of students in the learning process, seen from increased interaction, cooperation, and the ability to construct a storyline based on pictures. Thus, the application of the Picture and Picture model is effective in improving the quality of PAI learning, increasing student motivation, and strengthening the understanding of the exemplary values contained in the stories of the prophets.